Peran Lembaga Pemberdayaan Masyarakat Desa Dalam Meningkatkan Pembangunan Sanitasi Lingkungan Cisomang Barat - Tata Ayu Candika; Dedi Herdiana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this paper is to find out and analyze the reality of the role of the Village Community Empowerment Agency (LPMD) in improving the development of environmental sanitation in the West Cisomang Village. This study uses descriptive research method LPMD. The results of the study show: First, the efforts made by the Village Community Empowerment Institute (LPMD) to improve the development of sanitation in the West environment include: problem solving, participation in the development of environmental sanitation and the realization of partnerships with the Cisomang Barat village government. Second, a number of supporting factors and barriers to the efforts of the Regional Government Empowerment Empowerment Agency to improve the development of environmental sanitation with a participatory community empowerment process. Third, the achievement of the Village Community Empowerment Institute in improving the development of environmental sanitation is the achievement of environmental sanitation development in the Village of West Cisomang.